Optical-based sensors for monitoring corrosion of reinforcement rebar via an etched cladding Bragg grating - Adikan, Faisal Rafiq Mahamd; Abu Hassan, M.R.; Abu Bakar, M.H.; Dambul, K.D. (MDPI, 2012)
In this paper, we present the development and testing of an optical-based sensor for monitoring the corrosion of reinforcement rebar. The testing was carried out using an 80% etched-cladding Fibre Bragg grating sensor to monitor the production of corrosion waste in a localized region of the rebar. Progression of corrosion can be sensed by observing the reflected wavelength shift of the FBG sensor. With the presence of corrosion,the etched-FBG reflected spectrum was shifted by 1.0 nm. In addition, with an increase in fringe pattern and continuously, step-like drop in power of the Bragg reflected spectrum was also displayed.